A geometrically exact formulation of peridynamics - Javili, Ali; McBride, Andrew; Steinmann, Paul (Theoretical and Applied Fracture Mechanics, 2021)
The main objective of this contribution is to develop a geometrically exact peridynamics (PD) formulation wherein the basic elements of continuum kinematics are preserved. The proposed formulation accounts for large deformations and is variationally consistent. We distinguish between one-, two- and three-neighbour interactions. One-neighbour interactions recover the original (bond-based) PD formalism. Two- and three-neighbour interactions are fundamentally different to state-based PD. We account for material frame indifference and provide a set of appropriate arguments for objective interaction potentials accordingly. This contribution is presented in a manner such that the established theory is immediately suitable for computational implementation. From a computational perspective, the proposed strategy is fully implicit and the quadratic rate of convergence associated with the Newton–Raphson scheme is observed. Finally, we demonstrate the capability of our proposed framework via a series of numerical examples at large deformations.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Continuum kinematics; Geometrically exact; Large deformations; Peridynamics; Variationally consistent